Experimental investigation and thermodynamic calculations of the Bi-Ni-Pb phase diagram - Minić D.; Premović M.; Tošković N.; Manasijević D.; Ćosović V.; Janaćković M.; Tomović M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The article presents an experimental study of a phase diagram of a ternary Bi-Ni-Pb system using differential thermal analysis (DTA), scanning electron microscopy (SEM) with energy dispersive spectrometry (EDS), and X-ray powder diffraction (XRD) analysis. The investigated ternary alloys were selected from three vertical sections (x(Bi)=0.75, x(Ni)=0.1 and x(Pb)=0.9) and two isothermal sections at 100 and at 300°C. The obtained experimental results were compared with the thermodynamically extrapolated phase diagram of the Bi-Ni-Pb ternary system based on the thermodynamic parameters for the constitutive binary systems available in literature. Reasonably close agreement between the experimental data and the calculated phase diagram was obtained. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. OI172037]